Data structures and algorithms - Aho, Alfred V.; Hopcroft, John E.; Ullman, Jeffrey D. (Massachusetts : Addison-Wesley Publishing Company, 1983)
This book presents the data structures and algorithms that underpin much of today's computer programming.
Chapter 1. Design and analysis of algorithms -- Chapter 2. Basic data types -- Chapter 3. Trees -- Chapter 4. Basic operations on sets -- Chapter 5. Advanced set representation methods.
Includes bibliographical references and index.
Keywords: DATA STRUCTURES (COMPUTER SCIENCE); ALGORITHMS